Health System Quality Improvement: Impact of Prompt Nutrition Care on Patient Outcomes and Health Care Costs. Issue 3 (July 2016) - Meehan, Anita; Loose, Claire; Bell, Jvawnna; Partridge, Jamie; Nelson, Jeffrey; Goates, Scott
Abstract : Among hospitalized patients, malnutrition is prevalent yet often overlooked and undertreated. We implemented a quality improvement program that positioned early nutritional care into the nursing workflow. Nurses screened for malnutrition risk at patient admission and then immediately ordered oral nutritional supplements for those at risk. Supplements were given as regular medications, guided and monitored by medication administration records. Post–quality improvement program, pressure ulcer incidence, length of stay, 30-day readmissions, and costs of care were reduced.